PENGARUH PENERAPAN LEMBAR KERJA SISWA BERBASIS TANDUR TERHADAP PENCAPAIAN KOMPETENSI IPA SISWA KELAS VII SMPN 30 PADANG - Windy Putri Chania; Mahrizal Mahrizal; Zulhendri Kamus (Universitas Negeri Padang, 2016)
The still student achievement of competence IPA is caused by several factors, such as the learning process is teachers center, students grade in the learning process is a talk and worksheets have not been able to motivate students to learn. This grade aims to determine the effect of applying Student Worksheet TANDUR based on the achievement of competence IPA seventh grade students of SMPN 30 Padang.This research is a quasi-experimental research and the grade design used is randomizes Only Control Group Design. The population of this grade were all students of class VII semester of 2 in SMPN 30 Padang in the academic year 2015/2016. Sampling was done by using purposive sampling and cluster random sampling. The sample in this research is class VII-1 as the control class and VII-2 as a class experiment. The instrument used in this grade is the observation sheet to assess the competence Attitude Attitude, Knowledge written test for competence and scoring rubrics for skills competency. Data analysis technique used is the test hypotheses about the equality of two average and regression and correlation.The results of the data analysis is based on research that has been done shows the average value of the competence Knowledge, Attitudes and Skills in a row from the experimental class, namely: 83.750; 76.132; and 78.684. Control classes, namely: 79.044; 73.456; and 77.132. From the test results of the equality of two average on knowledge gained competence t count = 2.136 and t table = 1,998; the attitude of competence obtained t count = 2.284 and t table = 1.998; Skills and competencies obtained t count = 2.505 and t table = 1.998. In all three of these competencies obtained t count > t table, then t is outside the reception area of Ho, so Hi be accepted.Level relationship LKS value with the value of competence Knowledge is strong enough, and the effect of LKS at 30.82%. It can be concluded that the application of the Student Worksheet Based TANDUR provide significant impact on the real level of 0.05 against the Learning Outcomes Science Class VII SMPN 30 Padang on Competence Attitude, Knowledge and Skills